The role of information and communication technology in development of university education in Nigeria (2013)
Information and Communication Technologies (ICTs) play vital roles in the development of university education in Nigeria. They aid in the storage, retrieval, display, and dissemination of information. This study examined the importance of ICTs in achieving the mission and vision of university education in Nigeria. This was informed by the fact that ICT has become an invaluable tool for the enhancement of teaching, learning, and research; and also community service. ICT facilities are now becoming indispensable tools for development with positive effects of ICT noted in commerce and industry, education, politics and government, culture, and other aspects of human life. The use of the ICTs may make or mar the goals and objectives of university education. This paper reviews the concept of information technologies, its application to education, the prospects and the challenges facing utilization of ICTs in the universities. Most lecturers and other stakeholders are not able to use ICTs. The researchers therefore suggested that seminars and workshops should be organized to educate lecturers and stakeholders in the education industry to acquire the technical skills required to be able to apply lCTs to teaching, learning and research, and its essence in the development of university education.